Influence of demographic variable on quality of life among women in Ibadan metropolis, Oyo State of Nigeria (2016)
The issues of poor quality of life among Nigeria women results to inadequate participation of women in the development of the country, high rate of maternal death, increasing rate of mentally, physically challenge and high rate of financial handicap of Nigeria women, which have significant influence on the society at large attracted attention of this study. This study examined influence of demographic variable on quality of life among women in Ibadan metropolis, Nigeria. The study utilized cross-sectional research design which involves the use of self-report questionnaire for data collection. A total number of 600 women participated in the study. Results outcomes shows that marital status had significant influence on quality of life at (F (4/595) = 13.324, P<0.05). The result also revealed that religion income and occupation had significant influence on quality of life of women in Ibadan metropolis (F (2/597) = 7.267, P<0.05. F (7/592) = 4.905, P<0.05 & F (3/596) = 3.190, P<0.05). It was concluded that marital status, religion, educational attainment, income and occupation of women living in Ibadan metropolis significantly influence their quality of life. Therefore, this study recommends that women should seek to acquire more knowledge through their educational status and government should create conducive workplace climate and improve financial assistance programme to built economic status of Nigeria women